Effects of three variations of rule-example sequence in self-instructional materials on students understanding of mathematical concepts - Cayanong, Evangeline Hipe 1954- (1980)
In search of better strategies for teaching mathematical concepts, this study compared three strategies (CE-Characterization Exemplification, EC-Exemplification Characterization, and E-Exemplification) which are based on the moves suggested by Henderson in 1967 and studies on the generalization's effect on concept learning. Self-Learning Kits (SLK) were used to develop the concepts-arithmetic sequence, Fibonacci-like sequence, and geometric sequence. The study was conducted at the Divine Word University of Tacloban. Itwas concluded that the three strategies for teaching mathematical concepts do not have different effects on the student's understanding of concepts taught.
Vita.
Thesis (M.A. Mathematics Education)--University of the Philippines, Diliman.
Keywords: Mathematics -- Study and teaching (Secondary) -- Philippines -- Tacloban City (Leyte); Teaching -- Philippines -- Tacloban City (Leyte) -- Aids and devices